Advancing Rehabilitation Medicine with the Metaverse: Opportunities and Challenges - Rocco Salvatore Calabrò; Giovanni Morone (Brain Sciences)
The metaverse, an immersive virtual environment, is emerging as a transformative tool in rehabilitation, offering innovative modalities for motor and cognitive treatments. Virtual reality and augmented reality within the metaverse facilitate interactive exercises, allowing patients to perform rehabilitative tasks in a gamified context, which can improve motivation and adherence. Furthermore, the metaverse supports treatments that are not easy to carry out during conventional therapy, such as the rehabilitation of social participation, and creates a real individuals-based platform of continuum of care thanks to its interoperability. However, challenges such as technological accessibility, user adaptability, and the need for comprehensive clinical guidelines remain. Future research should focus on long-term efficacy, integration into traditional rehabilitation frameworks, and addressing ethical considerations, ultimately positioning the metaverse as a valuable adjunct in rehabilitative practices.